International Study of Primary Mucinous Ovarian Carcinomas Managed at Tertiary Medical Centers. Issue 5 (1st June 2018) - Mueller, Jennifer J.; Lajer, Henrik; Mosgaard, Berit Jul; Bach Hamba, Slim; Morice, Philippe; Gouy, Sebastien; Hussein, Yaser; Soslow, Robert A.; Schlappe, Brooke A.; Zhou, Qin C.; Iasonos, Alexia; Høgdall, Claus; et al.
Abstract : Objective: We sought to describe a large, international cohort of patients diagnosed with primary mucinous ovarian carcinoma (PMOC) across 3 tertiary medical centers to evaluate differences in patient characteristics, surgical/adjuvant treatment strategies, and oncologic outcomes. Methods: This was a retrospective review spanning 1976–2014. All tumors were centrally reviewed by an expert gynecologic pathologist. Each center used a combination of clinical and histologic criteria to confirm a PMOC diagnosis. Data were abstracted from medical records, and a deidentified dataset was compiled and processed at a single institution. Appropriate statistical tests were performed. Results: Two hundred twenty-two patients with PMOC were identified; all had undergone primary surgery. Disease stage distribution was as follows: stage I, 163 patients (74%); stage II, 8 (4%); stage III, 40 (18%); and stage IV, 10 (5%). Ninety-nine (45%) of 219 patients underwent lymphadenectomy; 41 (19%) of 215 underwent fertility-preserving surgery. Of the 145 patients (65%) with available treatment data, 68 (47%) had received chemotherapy—55 (81%) a gynecologic regimen and 13 (19%) a gastrointestinal regimen. The 5-year progression-free survival (PFS) rates were 80% (95% confidence interval [CI], 73%–85%) for patients with stage I to II disease and 17% (95% CI, 8%–29%) for those with stage III to IV disease. The 5-year PFS rate was 73% (95% CI, 50%–86%) for patients who underwent fertility-preserving surgery. Conclusions: Most patients (74%) presented with stage I disease. Nearly 50% were treated with adjuvant chemotherapy using various regimens across institutions. The PFS outcomes were favorable for those with early-stage disease and lower but acceptable for those who underwent fertility preservation.